Shoutfighting and other fiction - Rasmenike, Nonqubela Evelyn (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2020)
This document consists of three parts: Part A: English Half
Ingqokelela Yeentsomi-Mabali
Keywords: South African fiction (English) -- 21st century; Xhosa fiction -- 21st century